2021
DOI: 10.1080/09540105.2021.1934419
|View full text |Cite
|
Sign up to set email alerts
|

Immune enhancement effects of Korean ginseng berry polysaccharides on RAW264.7 macrophages through MAPK and NF-κB signalling pathways

Abstract: Ginseng, a commonly used medicinal herb, contains polysaccharide as one of the bioactive compounds. This study aimed at evaluating the immune enhancement effects of Korean ginseng berry polysaccharides (GBPs) on macrophage RAW264.7 cells and their chemical characteristics. The crude polysaccharide (GBP-C) was extracted and fractionated to different polysaccharides (GBP-F1, GBP-F2, and GBP-F3). GBPs were mainly composed of rhamnose, arabinose, mannose, glucose and galactose, with molecular weights (M w ) rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Previous studies have reported that plant extracts including AH extracts stimulated the production of NO in RAW 264.7 or macrophages [ 13 , 38 , 39 , 40 ]. NO is a well-known inflammatory mediator and is released from activated macrophages during an infection or inflammation [ 41 ]. The extract of AH leaves and roots and fermented AH roots significantly stimulated NO production by HD11 macrophages in a dose dependent manner [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that plant extracts including AH extracts stimulated the production of NO in RAW 264.7 or macrophages [ 13 , 38 , 39 , 40 ]. NO is a well-known inflammatory mediator and is released from activated macrophages during an infection or inflammation [ 41 ]. The extract of AH leaves and roots and fermented AH roots significantly stimulated NO production by HD11 macrophages in a dose dependent manner [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Korean ginseng berries were obtained from Boeun, Chungcheong Province, Korea. Korean GBPs with molecular weights of 328.4 and 54.2 × 10 3 (g/mol) comprising rhamnose (4.0%), arabinose (19.8%), mannose (2.2%), glucose (27.7%), and galactose (46.3%) were prepared as described in our previous report [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Polysaccharides from Korean ginseng after cellulase- and α-amylase-based extraction can enhance spleen and thymus indices, lymphocyte proliferation, leukocyte count, NK cell activity, and serum levels of IL-2 , IL-6 , and IFN-γ in CY-induced immunosuppressed mice [ 30 ]. Moreover, we recently reported that Korean ginseng berries show immune-enhancing effects in RAW 264.7 cells [ 31 ]. However, still little is known about the immunomodulatory effect of polysaccharides from Korean ginseng berry in CY-induced immunosuppressive mice model.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has identified crude and three fractionated polysaccharides isolated from Korean ginseng berries (GBPs: GBP-C, GBP-F1, GBP-F2, and GBP-F3) by an ion-exchange chromatography. In the analysis of these polysaccharides, gas chromatography-mass spectrometry (GC-MS) has been used to evaluate monosaccharides such as rhamnose, arabinose, mannose, glucose, and galactose [ 32 ]. Four fractions of polysaccharides have been shown to possess immune-enhancing activities by increasing the expression of iNOS , COX-2 , TNF-α , IL-1β , and IL-6 via NF-κB and MAPK signaling pathways [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the analysis of these polysaccharides, gas chromatography-mass spectrometry (GC-MS) has been used to evaluate monosaccharides such as rhamnose, arabinose, mannose, glucose, and galactose [ 32 ]. Four fractions of polysaccharides have been shown to possess immune-enhancing activities by increasing the expression of iNOS , COX-2 , TNF-α , IL-1β , and IL-6 via NF-κB and MAPK signaling pathways [ 32 ]. GBP-C can also boost immune function in mice [ 33 ].…”
Section: Introductionmentioning
confidence: 99%